Seismic to Geological Modeling Workflow, an Integrated Approache to Determine the Reservoir Quality of a Fractured Limestone: Oseil Field Example - Lapulisa, Arie K.; Andrianto, Roy; Dradjat, Anggoro S. (Berita Sedimentologi, 2012)
Natural fractured carbonate reservoir is extremely challenging in terms of reservoir characterization due to its high heterogeneity of reservoir property and also of its low oil recoveries. This paper will show how the integration of seismic data and well data had helped significantly for the well placement and also in the well completion stage.The datasets that are available and being used in this process are 3D seismic, seismic Inversion, seismic attributes, conventional log and borehole image log. All these data are being utilized in an integrated way to characterize the fractures behavior of the reservoir.